State Policy Responses to Ensuring Excellent Educators in Rural Schools - Douglas J. Gagnon; Marybeth J. Mattingly (Journal of Research in Rural Education, 2015)
The Excellent Educators for All initiative is the most recent federal policy effort to address unequal access to teacher quality in the United States. States were required to submit equity plans to the U.S. Department of Education that detailed how to ensure that poor and minority children do not receive instruction from less qualifi ed teachers. States could extend their plans to include rural students, although this was not a statutory requirement. Past federal reform efforts around raising teacher quality have been widely criticized as being overly prescriptive, and ultimately failing to account for the unique contexts of rural schools. We examine the extent to which rural needs are addressed in all available state equity plans. We fi nd that roughly half of U.S. states examine equity gaps along the urban-rural continuum, and roughly half propose rural-specifi c policy solutions to improve rural school staffi ng, although less than a third do both. States across the country employ a range of strategies in roughly equal measure, including grow your own programs, fi nancial incentives, communities of practice, and capacity building. In addition to detailing fi ndings and providing nuanced examples, this article also discusses implications for students and state policy.